2015
DOI: 10.3389/fnhum.2015.00243
|View full text |Cite
|
Sign up to set email alerts
|

Prism adaptation and spatial neglect: the need for dose-finding studies

Abstract: Spatial neglect is a devastating disorder in 50–70% of right-brain stroke survivors, who have problems attending to, or making movements towards, left-sided stimuli, and experience a high risk of chronic dependence. Prism adaptation is a promising treatment for neglect that involves brief, daily visuo-motor training sessions while wearing optical prisms. Its benefits extend to functional behaviors such as dressing, with effects lasting 6 months or longer. Because one to two sessions of prism adaptation induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…There were no adverse events or issues prohibiting continuation. Thus, even though the proposed dose via KF-PAT manual guidelines was not met, eight sessions can be interpreted as a successful implementation of the protocol because it was more than the suggested minimal dose (Goedert et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There were no adverse events or issues prohibiting continuation. Thus, even though the proposed dose via KF-PAT manual guidelines was not met, eight sessions can be interpreted as a successful implementation of the protocol because it was more than the suggested minimal dose (Goedert et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PA can be used to alleviate SN (64, 71, [80][81][82][83][84][85][86][87]. PA is dependent upon the mismatch between the perceived position of a target seen through prismatic goggles and its real position relative to the body (68).…”
Section: Pamentioning
confidence: 99%
“…Demonstrating that the experimental conditions used here are successful in inducing VMA is crucial first step in translating this research into new interventions for individuals with neglect. Additional studies will be required to determine the parameters that will give the greatest effect, similar to the call for studies to optimize the delivery of PA therapy [64].…”
Section: Optimizing Vmamentioning
confidence: 99%
“…Although this after-effect eventually wears off (deadaptation), studies examining the long-term treatment benefit of PA therapy have shown the effect to last up to 6 months with multiple sessions [64]. Limitations of PA therapy include visual disorientation, nausea, and boredom leading to lack of engagement and motivation [65].…”
Section: Introductionmentioning
confidence: 99%